DIABETIC FOOT PROBLEMS - Nather, Aziz (World Scientific, 2008)
This pioneering textbook is the first one ever on diabetic foot problems. With contributions from a multidisciplinary panel of experts, it presents a comprehensive curriculum on the topic. This includes global and socio-economic aspects of diabetes; a team approach; basic science of the foot (anatomy and biomechanics); clinical assessment and classification systems for diabetic foot problems; endocrine aspects; diabetic foot infections (clinical presentation and management); amputations in diabetic foot surgery (predictive factors, major and distal amputations, rehabilitation and phantom pain management); care of diabetic wounds (including the role of the latest technologically advanced dressings, vacuum dressings, anodyne therapy, ultrasonic debridement and extracorporeal shockwave therapy); and diabetic footcare and diabetic footwear.